2019
DOI: 10.1002/jcp.29291
|View full text |Cite
|
Sign up to set email alerts
|

circRNA‐associated ceRNA network construction reveals the circRNAs involved in the progression and prognosis of breast cancer

Abstract: Recently, increasing evidences show that circular RNAs (circRNAs) are important regulators of various diseases, especially cancer. However, the regulatory role and the potential mechanism of action of circRNAs in breast cancer remain largely unknown. In this study, weighted gene co-expression network analysis was conducted with the differentially expressed miRNAs and mRNAs in breast cancer from The Cancer Genome Atlas database to identify the key modules associated with the carcinogenesis of breast cancer. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…Emerging evidence shows that circRNAs are tightly associated with the occurrence of malignant tumors, and their dysfunction could inhibit tumor growth and metastasis. 16,17 For example, Huang et al 18 discovered that circRNA_100876 was dysregulated in esophageal squamous cell carcinoma, and that its expression was closely linked to clinical progression, suggesting that it could be a promising prognostic biomarker. These studies, together with the current results, suggest that circRNA_100395 may be a potential therapeutic biomarker and target in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence shows that circRNAs are tightly associated with the occurrence of malignant tumors, and their dysfunction could inhibit tumor growth and metastasis. 16,17 For example, Huang et al 18 discovered that circRNA_100876 was dysregulated in esophageal squamous cell carcinoma, and that its expression was closely linked to clinical progression, suggesting that it could be a promising prognostic biomarker. These studies, together with the current results, suggest that circRNA_100395 may be a potential therapeutic biomarker and target in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that circRNAs play a vital role in modulating tumor development by maintaining cellular homeostasis. 16 The involvement of circRNAs in different types of cancers has also been reported. 17 They can play a role of regulatory interaction with miRNA to prevent mRNA translation, bind to RNA-associated proteins or influence gene expression by regulating gene splicing or mRNA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNA (circRNA) is a non-coding RNA with a special circular structure and high stability in eukaryotic cells (Li et al, 2018;Patop et al, 2019). Researchers have confirmed that circRNA can be used as a competitive endogenous RNA (ceRNA) for microRNA (miRNA) to regulate the expression of downstream targets (Ma et al, 2020). Studies have found that circRNA is closely related to the progression of a variety of cardiovascular diseases, including AMI (Altesha et al, 2019;Gong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%